Peri-Operative Outcomes Comparison of General Anaesthesia and Brachial Plexus Block for Open Reduction Internal Fixation of Metacarpal Fractures. Issue 1 (February 2022) - Budden, Curtis; Donaldson, Elsa Kaley; Tredget, Edward; Tsui, Ban C. H.
Introduction: Brachial plexus blockade (BPB) is a procedure of growing popularity amongst surgeons and anaesthesiologists involved with upper limb surgery. The safety and benefit in hand surgery is unclear. Methods: A retrospective chart review was performed examining all operative hand cases over a 2-year period. All cases of metacarpal open reduction internal fixation (ORIF) were included. Cases were excluded if paediatric patient, additional procedures performed, and/or a decreased LOC. Parametric statistical tests were performed. Results: In total, 54 cases with general anaesthesia (GA) and 48 cases with BPB were identified for the study (n = 102). The average total time from operating theatre to discharge was 245 ± 72 minutes in GA group and 195 ± 54 minutes in BPB ( P < .001). Of those who had a GA, 47/54 patients required analgesia post-operatively versus 12/48 in the BPB ( P < .001). Of all, 25/52 and 5/48 patients required anti-emetics post-operatively in the GA and BPB groups, respectively ( P < .001). Need for any parenteral medication post-operatively was also significantly different ( P < .001). Conclusion: This is the first study to specifically examine anaesthetic techniques for ORIF of hand fractures; adding to the body of literature establishing BPB as a safe and efficient method of anaesthesia.